Aerobic Training Modulates the Effects of Exercise-Induced Oxidative Stress on PON1 Activity: A Preliminary Study - Aneta Otocka-Kmiecik; Marek Lewandowski; Urszula Szkudlarek; Dariusz Nowak; Monika Orlowska-Majdak (The Scientific World Journal)
The aim of the study was to compare the effect of maximal exercise (ME) on paraoxonase (PON) and arylesterase (ARE) activity depending on lifestyle in respect to physical activity. The study was performed on 46 young men divided into two groups: sedentary (S) and physically active (PA). All participants performed ME on a treadmill. PON1 activities, FRAP, uric acid, bilirubin, TBARS, and lipid profile were determined in their blood before, at the bout of, and after ME. No significant differences in PON1 activities were found between S and PA subjects at baseline. Nearly all biochemicals increased at ME in both groups. Both PON and ARE activity increased at the bout of ME in PA subjects and only ARE activity in S subjects. ARE/HDL-C ratio increased at the bout of ME in PA and S subjects. The difference in PON1 activity response to ME between study groups may be a result of adaptation of PA subjects to regular physical activity. We suggest that PON1 activity may be a marker of antioxidant protection at ME and an indicator of adaptation to exercise.